Financial contracting and misreporting with limited enforcement, firm financing and growth - Adams Sorekuong Yakubu Adama (Cogent Economics & Finance, 2020)
This article employs a dynamic stochastic general equilibrium framework to examine asymmetric information and limited contract enforcement in financial markets, where firms have access to both internal and external sources of finance. It considers limited enforcement of financial contract in the form of firm's ability to misreport and default on output when it is still solvent, that is, a form of institutional weaknesses in holding defaulters to account. The model shows how institutional weakness in the form of limited enforceability of financial contracts affects fluctuations in key macroeconomic variables such as output, employment and investment via its impact on interest rates, risk premium, default risk and leverage. The findings show that limited contract enforcement amplifies the effects of shocks and lower small firm funding. The sensitivity analysis shows that weak contract enforcement affects firm growth and also leads to welfare losses to the society. This study is relevant for developing countries, where there is often poor quality of institutions and the paper suggests that improving such quality has the potential to improve the prospects of such countries.
Keywords: B26; D86; E32; K12; K42; O43; 330; Contracting; institutional weakness; limited enforcement; misreporting; financing